KEANEKARAGAMAN SPESIES DALAM SISTEM AGROFORESTRI DI DESA SURAJAYA KECAMATAN PEMALANG KABUPATEN PEMALANG JAWA TENGAH - Roziaty, Efri; Pristiwi, Yunitisia (Bioeksperimen: Jurnal Penelitian Biologi, 2020)
Agroforestry is sustainable land management system which integrate the yields of crops including trees and forest plants to increase the yields.This research intend to knowing the diversity type of vegetation in Desa Surajaya, Pemalang, Jawa Tengah. The research use exploration method by exploring all the research site and take the sample using purposive sampling method. The research done by exploring all the forest area and take a note for every new kind of vegetation. Research result shown that there are 19 kind of different vegetation, which is divided by a horticulture and non-horticulture. Forest land cleared for agriculture by agroforestry was 287,89 Ha or as much as 19,4% of the total forest area leaving 1.193,41 Ha of teak forest area.